Investigation of Denitrifying Phosphorus Removal Organisms in a Two-Sludge Denitrifying Phosphorus Removal Process - Zou, Haiming; Lu, Xiwu; Shi, Jing (Asian Journal of Chemistry, 2013)
Denitrifying phosphorus removal organisms in activated sludge samples from a two-sludge denitrifying phosphorus removal process for enhanced biological phosphate removal were investigated by fluorescence in situ hybridization, scanning electron micrograph and energy dispersive spectrometry. The fluorescence in situ hybridization showed that Candidatus accumulibacter phosphatis was dominant in the two-sludge denitrifying phosphorus removal process. By scanning electron micrograph, the morphology of denitrifying phosphorus removal organisms seemed to belong to length streptococcus and its sizes were significantly smaller in anaerobic environment than in anoxic environment. By energy dispersive spectrometry, the phosphorus content of activated sludge collected in this process studied here was 12.3 % of dry weight significantly higher than 3 % in traditional biological phosphorus removal process.